Natural course of Finnish gelsolin amyloidosis. (18th August 2015) - Nikoskinen, Tuuli; Schmidt, Eeva-Kaisa; Strbian, Daniel; Kiuru-Enari, Sari; Atula, Sari
Abstract : Background. Finnish type of hereditary gelsolin amyloidosis (FGA) is one of the most common diseases of Finnish disease heritage. Existing FGA knowledge is based only on smaller patient series, so our aim was to elucidate the natural course of the disease in a comprehensive sample of patients and to build up a national FGA patient registry. Methods. An inquiry about the known and suspected signs of FGA, sent to the members of Finnish Amyloidosis Association, telephone contacts, and hospital records were utilized to create the registry. Results. A total of 227 patients were entered to the database. The first symptom was ophthalmological for 167 patients (73.6%) at the mean age of 39 years. Corneal lattice dystrophy (CLD) was reported at the mean age of 43 years. Impaired vision, polyneuropathy, facial nerve paresis, and cutis laxa appeared on average between 52 and 57 years. Carpal tunnel syndrome (CTS) was reported by 86 patients (37.9%). Nine patients (4.0%) had a pacemaker, and 12 (6.1%) had cardiomyopathy. Conclusions. The first symptom was ophthalmological in most cases. Except for CLD no prominent difference in the age of appearance was found between the major symptoms. CTS, cardiac pacemakers, and cardiomyopathy were remarkably more common compared to the general population.